Critical Discourse Analysis of Clinton’s Orations at Presidential Elections in 2016 - Masoud dehghan; Behnaz vahabian (Journal of Political Studies, 2018)
This study aims at critical analysis of the orations of the candidate of democrat party, Clinton, at presidential elections of America. It has been done based on her independent orations and also her last face to face debate with Trump, the candidate of Republic party. In this sense, data analysis has been carried out not only based on the used key words by herself in the orations but also the selection of the theme of speech at odds with the other by using comparative approach in which we have focused on the analysis of the selective words used in the last debate. Also, the findings indicate the most use of four themes of security, nationalism, women and justice among which justice and equality themes have been considered as the nodal point and the theme of women's rights as the empty signifier.